Copper Transporter ATP7A (Copper-Transporting P-Type ATPase/Menkes ATPase) Limits Vascular Inflammation and Aortic Aneurysm Development: Role of MicroRNA-125b. Issue 11 (November 2019) - Sudhahar, Varadarajan; Das, Archita; Horimatsu, Tetsuo; Ash, Dipankar; Leanhart, Silvia; Antipova, Olga; Vogt, Stefan; Singla, Bhupesh; Csanyi, Gabor; White, Joseph; Kaplan, Jack H.; Fulton, David; et al.
Abstract : Objective: Copper (Cu) is essential micronutrient, and its dysregulation is implicated in aortic aneurysm (AA) development. The Cu exporter ATP7A (copper-transporting P-type ATPase/Menkes ATPase) delivers Cu via the Cu chaperone Atox1 (antioxidant 1) to secretory Cu enzymes, such as lysyl oxidase, and excludes excess Cu. Lysyl oxidase is shown to protect against AA formation. However, the role and mechanism of ATP7A in AA pathogenesis remain unknown. Approach and Results: Here, we show that Cu chelator markedly inhibited Ang II (angiotensin II)–induced abdominal AA (AAA) in which ATP7A expression was markedly downregulated. Transgenic ATP7A overexpression prevented Ang II–induced AAA formation. Conversely, Cu transport dysfunctional ATP7A mut/+ /ApoE −/− mice exhibited robust AAA formation and dissection, excess aortic Cu accumulation as assessed by X-ray fluorescence microscopy, and reduced lysyl oxidase activity. In contrast, AAA formation was not observed in Atox1 −/− /ApoE −/− mice, suggesting that decreased lysyl oxidase activity, which depends on both ATP7A and Atox1, was not sufficient to develop AAA. Bone marrow transplantation suggested importance of ATP7A in vascular cells, not bone marrow cells, in AAA development. MicroRNA (miR) array identified miR-125b as a highly upregulated miR in AAA from ATP7A mut/+ /ApoE −/− mice. Furthermore, miR-125b target genes (histone methyltransferase Suv39h1 and the NF-κB negative regulator TNFAIP3 [tumor necrosis factor alpha induced protein 3]) were downregulated, which resulted in increased proinflammatory cytokine expression, aortic macrophage recruitment, MMP (matrix metalloproteinase)-2/9 activity, elastin fragmentation, and vascular smooth muscle cell loss in ATP7A mut/+ /ApoE −/− mice and reversed by locked nucleic acid-anti-miR-125b infusion. Conclusions: ATP7A downregulation/dysfunction promotes AAA formation via upregulating miR-125b, which augments proinflammatory signaling in a Cu-dependent manner. Thus, ATP7A is a potential therapeutic target for inflammatory vascular disease. Abstract : Supplemental Digital Content is available in the text.